2020
DOI: 10.3389/fmicb.2020.555347
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis in the Dead: Human Postmortem Microbiome Beta-Dispersion as an Indicator of Manner and Cause of Death

Abstract: Beta-Dispersion Reflects Forensic Death Determination wound). We propose an analytical workflow that combines postmortem microbiome indicator taxa, beta-dispersion, and case demographic data for predicting MOD and COD classifications. Overall, we provide further evidence the postmortem microbiome is linked to the host's antemortem health condition(s), while also demonstrating the potential utility of including beta-dispersion (a non-taxon dependent approach) coupled with case demographic data for death determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…The PMI and cause of death were associated with the alpha and beta diversity of the tissue microbial profiles (Lutz et al, 2020). Similar associations were observed previously where the beta dispersion differed significantly between anatomical body sites and causes and manners of death (Kaszubinski et al, 2020b). A different microbial signature was also observed in cardiovascular disease cases.…”
Section: Dysbiosis In Cause Of Deathsupporting
confidence: 83%
“…The PMI and cause of death were associated with the alpha and beta diversity of the tissue microbial profiles (Lutz et al, 2020). Similar associations were observed previously where the beta dispersion differed significantly between anatomical body sites and causes and manners of death (Kaszubinski et al, 2020b). A different microbial signature was also observed in cardiovascular disease cases.…”
Section: Dysbiosis In Cause Of Deathsupporting
confidence: 83%
“…In a recent study to determine how postmortem microbiome beta dispersion could be an additional forensic tool for predicting cause and manner of death in medicolegal investigations, a surprising finding demonstrated that the beta diversity significantly differed among body sites and causes and manners of death. For example, microorganisms detected in cardiovascular disease cases had significantly increased beta dispersion among all body locations (eyes, ears, nose, rectum, and mouth) ( Kaszubinski et al, 2020 ). Therefore, the increase in microorganisms in cardiovascular disease cases demonstrates dysbiosis in the dead, and that microbial signature variability may be measured through beta-dispersion calculations (e.g., Kruskal–Wallis).…”
Section: Discussionmentioning
confidence: 99%
“… Kaszubinski et al (2020) modeled beta-dispersion to test for manner and cause of death association using a microbiome data set of n = 188 postmortem cases (five body sites per case). The researchers demonstrated that beta-dispersion and demographic data could distinguish among manner and cause of death.…”
Section: Major Themes In the Forensic Microbiology Literaturementioning
confidence: 99%